Mysteries of mankind [videorecording] - Jampel, Barbara; Kane, Dennis B.; Skinner, Thomas (National Geographic Society special, 1988)
Traces the development of human evolution and establishes relationships among ancestral species. Explains evolution in association with tool making from human paleontological studies in Africa, England, and Israel.